Children in Digital Age – International Regulations - Savčić, Sanja (Children in Digital Age, 2025)
Abstract:The advent and rapid development of computer technology have revolutionised human society. In a remarkably short period, technology has transformed daily life, shifting from occasional computer use to the Internet as the primary channel of communication, and now to artificial intelligence, which enables machines to mimic human behaviour and decision-making. Historically, such profound changes took centuries; today, they are occurring at an unprecedented pace, leaving many struggling to adapt. While digitalisation has made technology more user-friendly and widely accessible across generations, disparities in digital skills persist. Younger generations often fully grasp the potential of digital technology, while their parents may lack equivalent expertise. This reality is creating a widening generational gap, even more pronounced than in previous decades. Children are particularly adept at using innovative technologies, especially the Internet, yet they may not fully understand the real-world consequences of their online activities. Conversely, parents are generally more aware of the associated risks and dangers, though they often lack the same technical proficiency. Growing up in a more traditional society, these older generations may feel somewhat constrained by the pervasive digitalisation of life. While they observe the process of digital integration, they do not always participate actively. From the perspective of children’s rights, this new age poses challenges for scholars and legislatures alike. Although it is tempting to examine each right in isolation, certain rights are particularly difficult to enforce in the digital realm. This work will explore these rights in detail.Keywords: digital age, children’s rights, right to privacy, right to education, right to be informed